P250 Interim analysis of individual risk factors, sexual networks, and STI risk in a military population. (14th July 2019) - Magno, Nicholas; Garges, Eric; Kao, Tzucheg; Smith, Realisha; Lalani, Tahaniyat
Abstract : Background: Sexually transmitted infections (STIs) are a consistent medical concern among military service members, who may experience select rates well above their civilian counterparts. Differences in individual risk behaviors as well as network risk factors are different in military populations which may explain the increased rates of select STIs. We performed a pilot study to validate a STI risk assessment survey tool for future use in the military population. Methods: Naval Medical Center Portsmouth was used to pilot a survey for a larger, egocentric social, and sexual network study in military populations. Study participants (n=50) completed an anonymized computer-assisted survey focusing on STI risk factors, including a sexual partner inventory. We evaluated individual demographics, behavioral risk factors, and sexual partnership formation to include mixing patterns and concurrency. Recent history of STI was self-reported in the survey and validated with the participant's medical record. Fischer's exact test was used if applicable. For partners, data was weighted and Wald Chi-square test was used to assess association between variables. Results: Completion of the survey and sexual inventory by respondents was common. The majority were active duty, enlisted, and male. The survey suggested evidence of concurrency and disassortive mixing by age, race, and active duty status. Respondent (p=0.0089) and sexual partner (p=0.0401) alcohol consumption before sex was common and associated with history of STI. Condom use was inconsistent and less frequent with main/steady partners when compared to casual and anonymous partners. Conclusion: The high completion rate demonstrated in this pilot study support that a military population will complete a detailed STI risk index including sexual partner inventory. Interim data analysis suggests that common individual risk factors such as network/partnership risk factors can be analyzed using an egocentric survey design. These results will have future implications for targeted prevention programming in the U.S. Military. Disclosure: No significant relationships.